Measurement Of CEO Confidence : A Literature Review - Mohd Waliuddin, Mohd Razali; Dg. Juaidah, Awang Jambol; Damien Lee, Lung Yau; Anuar, Muhammad (QJSSH, 2024)
Chief Executive Officer (CEO) confidence influences decision-making processes, includinginvestment strategies, expansion plans, and organizational efforts, providing an indication of the overall sentiment and future outlook of business leaders. CEO confidence strongly influences strategic decisionmaking, pushing employees and stakeholders to pursue ambitious growth plans. When CEO confidence diminishes, it often leads to a more cautious approach to decision-making within the company. This caution can result in delayed or scaled-back investment initiatives, hindering the company's ability to seize growth opportunities and respond effectively to market fluctuations, thereby dampening both internal morale and external stakeholder confidence in the company's prospects. Tracking CEO confidence indicators offers vital insights for investors and organizations to make informed decisions and handle the ever-changing business climate efficiently. Discuss all CEO confidence measurement methods based on previous research in the paper. The CEO confidence measurement can be categorized into six groups: option, net buyer, photo, reward, finance behavior, and media press. Future research may explore additional measurement categories to enhance understanding of CEO confidence dynamics and its implications for strategic decision-making and organizational performance.